2021
DOI: 10.3390/polym13111782
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Two-Dimensional Magnetostrictive Fillers of CoFe2O4-Intercalated Graphene Oxide Sheets in 3-2 Type Poly(vinylidene fluoride)-Based Magnetoelectric Films

Abstract: In the last decade, magnetoelectric (ME) polymer films have been developed by including zero-dimensional or one-dimensional magnetostrictive fillers in a piezoelectric polymer matrix. Existing reports on ME polymer films reveal that the shape of the magnetostrictive fillers is a critical determinant of the polymeric phase conformation, strain transfer between the piezoelectric and magnetostrictive phases, and dipole alignment in the films. In this study, to investigate the effect of two-dimensional (2D) magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Polar β-phase crystals in piezoelectric polymers are aligned along the direction of the applied electric field, which can lead to high piezoelectric outputs . In this procedure, a corona poling method was used for the effective polarization of thinly coated P­(VDF-TrFE) films on Ni foams. , The corona poling process was performed in a homemade corona poling system for 1 h at 120 °C under an applied DC voltage of 10 kV to obtain poled composites. The distance between the needle and the sample was 1 cm.…”
Section: Methodsmentioning
confidence: 99%
“…Polar β-phase crystals in piezoelectric polymers are aligned along the direction of the applied electric field, which can lead to high piezoelectric outputs . In this procedure, a corona poling method was used for the effective polarization of thinly coated P­(VDF-TrFE) films on Ni foams. , The corona poling process was performed in a homemade corona poling system for 1 h at 120 °C under an applied DC voltage of 10 kV to obtain poled composites. The distance between the needle and the sample was 1 cm.…”
Section: Methodsmentioning
confidence: 99%
“…An interesting study was published by Baek and Yang [307] who reported the application of CoFe2O4-intercalated GO as -2D magnetostriction (i.e. changing shape or dimension during magnetization) PVDF fillers.…”
Section: Practical Applications Of Pvdf-cnms In Various Generatorsmentioning
confidence: 99%
“…ME sensors, which are based on the magnetoelectric coupling effect, can timely transmit magnetic field signals as voltage, mediated by interfacial stress ( ) [ 3 , 22 , 23 , 24 , 25 ]. A good ME sensor should have a high ME coupling coefficient ( ); thus, large output voltage is available under a certain external magnetic field.…”
Section: Introductionmentioning
confidence: 99%